(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Plant physiological parameters such as membrane thermostability, canopy temperature depression, leaf chlorophyll content and yield related traits like no. of spikelets per spike, no. of grains per spike, 200-grain weight and grain yield of 18 wheat genotypes were carried out to assess for heat tolerance. Performances of all the genotypes were found to have significant differences for all the traits except canopy temperature depression. But, canopy temperature depression with some other traits like leaf chlorophyll content, no. of grains per spike, 200-grain weight and grain yield per plant demonstrated significant differences when it grown in heat stress condition. In general, genotypes with higher leaf chlorophyll content and enhanced membrane thermostability demonstrated higher 200-grain weight or grain yield. Besides, in spite of having heat tolerant traits, several genotypes performed poor due to their poor genotypic potential. The present investigation has successfully isolated several genotypes viz. H024, H023, H022 and H018 with desirable traits related to heat tolerance based on overall performance while grown under heat stress. These genotypes can be used as gene source for future breeding program to improve heat tolerance of the local wheat cultivars. J. Bangladesh Agril. Univ. 16(3): 457–463, December 2018